Antibacterial activity of Apis mellifera bees honey, garlic extracts and their combinations against Salmonella in Wolayta Sodo, Southern Ethiopia - Wolde, Rediet; Mahamed, Samatar Abshir (Svāsthya: Trends in General Medicine and Public Health, 2024)
The global emergence of antibiotic-resistant Salmonella strains poses a significant threat to public health, necessitating the development of alternative antimicrobial agents. Although natural substances, such as honey and garlic, have shown promise in combating various pathogens, their efficacy against Salmonella, particularly in combination, remains understudied. This study aimed to evaluate the antibacterial activity of Apis mellifera honey, garlic extracts, and their combination against Salmonella in Wolayta Sodo, southern Ethiopia. Aqueous honey and garlic extracts were prepared at concentrations of 25, 50, and 100 g/100 mL. Antibacterial activity against Salmonella was assessed via the agar well diffusion method to measure zones of inhibition. The efficacies of honey, garlic, and their combinations were compared at different concentrations. All the data were statistically analyzed via one-way ANOVA, with a probability of 0.05 and a 95% significance level, via SPSS Inc. Chicago, IL version 21.0. Honey exhibited the strongest antibacterial activity against Salmonella, with inhibition zones ranging from 13.67 mm to 26.33 mm across all concentrations. Garlic extracts showed moderate efficacy, producing inhibition zones between 12.00 mm and 15.67 mm. Unexpectedly, the combination of honey and garlic did not have synergistic effects and consistently underperformed compared with honey alone. The antibacterial activity of all the treatments was concentration dependent, with the highest efficacy observed at 100 g/100 mL (P<0.001). This study provides evidence of the potent antibacterial activity of Apis mellifera honey against Salmonella, which surpasses that of garlic extracts alone or in combination. These findings highlight the potential of honey as a natural antimicrobial agent, particularly at high concentrations.